2013
DOI: 10.1007/s00128-013-1083-7
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Three Selected Endocrine Disrupting Chemicals on the Fecundity of Fruit Fly, Drosophila melanogaster

Abstract: Bisphenol A (BPA), 4-nonylphenol (4-NP) and 4-tert-octylphenol (4-tert-OP) are the endocrine disrupting chemicals (EDCs) that has been shown to exert both toxic and biological effects on living organisms. The present study investigated effects of environmentally relevant concentrations of BPA, 4-NP and 4-tert-OP (0.1, 1 and 10 mg/L) on the fecundity of fruit fly Drosophila melanogaster. In the all exposure groups of BPA, 4-NP and 4-tert-OP, it was found a statistically significant decrease in mean fecundity as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…The fecundity of these exposed females is also reduced and their eggs are defective in maternal transcripts and proteins ( Vimal et al, 2019 ). The negative effect of BPA on female fertility was also observed in another Drosophila melanogaster study ( Atli, 2013 ). To test the maternal effect of BPA exposure on fly reproductive function, we exposed Drosophila melanogaster females to environmetally relavant concentrations (0, 0.1, 1, and 10 mg/L) of BPA and crossed with non-exposed males on the standard fly food without BPA.…”
Section: Resultssupporting
confidence: 67%
“…The fecundity of these exposed females is also reduced and their eggs are defective in maternal transcripts and proteins ( Vimal et al, 2019 ). The negative effect of BPA on female fertility was also observed in another Drosophila melanogaster study ( Atli, 2013 ). To test the maternal effect of BPA exposure on fly reproductive function, we exposed Drosophila melanogaster females to environmetally relavant concentrations (0, 0.1, 1, and 10 mg/L) of BPA and crossed with non-exposed males on the standard fly food without BPA.…”
Section: Resultssupporting
confidence: 67%
“…Results obtained in Drosophila melanogaster showed that EE exposure revealed potential toxic and endocrine effects on adults of both sexes (Bovier et al, 2018 ). NP has been described as an endocrine disrupter in other insect species (Atli, 2013 ; Yuan et al, 2013 ) and in mollusks (Riva et al, 2010 ; Liu et al, 2011 ; De Lisa et al, 2013 ). The mechanism by which NP interferes with the hormonal system is unknown, but its effect as an endocrine disruptor is attributed to its molecular structure since it is like estradiol (Thiele et al, 1997 ).…”
Section: Resultsmentioning
confidence: 99%
“…Exposure to BPA has been associated with a variety of toxic responses including strong reproductive effects across a variety of organisms through mechanisms that are sometimes distinct from its weak affinity for the estrogen receptor (ER). BPA’s reproductive effects can be considered hallmarksof its toxicity as BPA exposure leads to a decrease in fertility that correlates with a decreased viability of germ cells in a great number of animal species examined to date, including humans and well-established laboratory model organisms such as mouse, rat, zebrafish, drosophila, and C. elegans worms. , The mechanisms underlying BPA’s reproductive effects are also well conserved as BPA exposure was shown to cause an increase in germ cell death by apoptosis and an increase in chromosome errors and lethality in mouse and C. elegans early embryos. ,, In C. elegans , these findings were extended to the BPA analogue BPS, suggesting that the similarity in chemical structure imparts comparable effects on germ cells . The remarkable conservation of reproductive toxicity outcomes caused by BPA exposure was leveraged here to examine whether MnP-mediated degradation of BPA and its analogues decreases their associated toxicity by monitoring the model organism C. elegans .…”
Section: Resultsmentioning
confidence: 99%